The Survey of Physical Education Teachers’ Viewpoints on Causes and Prevalence of Sport Injuries at Schools - hassan ghadimi ilkhanlar; ramin Baloochi; mohammadreza Niknejad (Sport Sciences and Health Research)
The purpose of this study was to survey physical education teachers’ viewpoints on sport injuries at schools. Viewpoints of 83 physical education teachers (mean age: 35.32±2.58 years, mean work experience: 12±6.42 years) who were directly working with students at schools were collected by a researcher-made questioner and interview. Data were analyzed by descriptive statistics. The results showed that most physical education teachers (38.6%) believed that contusion was the most prevalent injury at schools. Also, most physical education teachers (67.5%) believed that most injuries happened in lower limbs at schools. 40.9% believed that the most important external factor of injuries was non-standard playground and 37.4% believed that the most important internal factor of injuries was a lack of body fitness. 72.2% of teachers believed that the most important factor of injuries was traumatic mechanism at schools.